Analisis Strategi Komunikasi Pemasaran Nibras House Wanasari Brebes Pada Media Sosial Tiktok - Solikha Pujirahayu; Ike Desi Florina; Inas Sany Muyassaroh (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
This study aims to analyze the marketing communication strategy used by Nibras House Wanasari on the Tiktok social media platform. This study will examine how Nibras House Wanasari utilizes Tiktok to promote its products and increase sales. Tiktok is one of the social media that continues to grow rapidly, and has great opportunities for entrepreneurs or marketers to interact with audiences directly or indirectly. By utilizing the AIDA marketing concept (Attetion, Interest, Desire, Action) Nibras House Wanasari has succeeded in attracting the attention of the audience with interesting content, arousing interest, creating desire, and encouraging active action. The method used in this study is a literature study with a qualitative approach. Researchers apply the AIDA marketing strategy to assess the effectiveness of content and live streaming in driving consumer behavior and considering the impact of the strategy on sales interest and brand awareness.